Contextual Meaning on the Idiomatic Expressions in the Novel Before the Coffee Gets Cold - Syahwa Indah Kirana; La Sunra; Abdullah Abdullah (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
The novel written by Toshikazu Kawaguchi with the title Before the Coffee Gets Cold uses a Japanese background, or rather Tokyo. The author explains that there is one located in a small alley in Tokyo. The age of the cafe is long enough or even you could say it's quite old. This research aims to identify idiomatic expressions in the novel. Idiomatic expression is a type of informal language which has a different meaning from the meaning of the words in that expression. “Hold Your Tongue” this idiom does not actually mean that you have to put your finger in your mouth and hold your tongue, it means that you should not talk. The theory used in this research is the theory from McCarthy and O'Dell (2010), where McCharty and O'Dell proposed 7 types of idioms, namely: similes, binomials, trinomials, euphemisms, proverbs, cliches, and fixed statements. This research uses a qualitative data analysis method based on Miles, Huberman and Saldana (2014). Data was taken from Toshikazu Kawaguchi's novel "Before the Coffee Gets Cold" and analyzed by reading the novel as much as possible and understanding all the conversations. The researcher categorized several conversations into types of idioms in the novel Before the Coffee Gets Cold. The results of this research show that there are 24 examples of simile in the text. In idiom Binomial, there are 11 examples of binomial in the text. In idiom Proverbs, there are 4 examples of binomial in the text.  In idiom trinomial, there are no examples of trinomials in the text. In idiom euphemism, there are no examples of euphemisms in the text. In idiom cliché, there are 6 examples of binomial in the text. And the last, idiom Fixed statements there are 13 examples of binomial in the text. In all these types of idioms, contextual meaning is how the use and combination of these words provide color, nuance, and additional meaning in the text. They help to depict situations, characters, or messages in the story more deeply and creatively.Keywords: idiom, idiomatic expression, novel